Silver Belt Collection from the Treasury Museum of Mother See of Holy Etchmiadzin - Chookaszian, Satenik (History and Culture, 2022)
In the XIX-XX centuries, belt was an important part of the Armenian folk costume. Silver belts were created in different areas of Western and Eastern Armenia. They varied from one another by the form of clasps, decoration, and often in creation techniques.The silver collection of the Treasury of Mother See of Holy Etchmiadzin is unique in terms of its richness and variety. The purpose of this article is to study the silver belts of the Treasury that have not been examined before.Among the women's belts of the Treasury, there is one with a butterfly-ribbon clasp (199), which repeats the structure of Vaspurakan belts, but the decoration of it seems to be pretty similar to another one that was created in Kars.From the men's belts collection, it is worth mentioning the one decorated with the image of a kinto (258) that has the surname of the master preserved - "М АИРАПETOBЪ". During our research, we had found five belts created by the same silversmith in different museums in Armenia. In fact, so far this is the largest collection known to us being created by the same master and consisting of diverse types of belts. In our opinion, this silversmith is Mkrtich Nikoghos Ayrapetov, who worked in the Armenian market of Tbilisi (Georgia) during 1893-1914.One of the men's belts in the Treasury is decorated with a depiction of a crown. During the research, we found several other belts with such decoration. Probably such "Crown Belts" were created for high-ranking people by special order.Each of the belts of the Treasury collection has unique difference/s from similar ones kept in other museums, which testifies to the skill and mastery of our silversmiths.
Keywords: Treasures of Etchmiadzin; Jewelry of Etchmiadzin; silver jewelry; silver belts; silversmiths; silversmith schools; history of silversmithing